EFEKTIVITAS PELAYANAN PUBLIK MELALUI PENERAPAN PELAYANAN ONLINE KARTU KELUARGA BAGI MASYARAKAT KELURAHAN ATAKKAE PADA KANTOR KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN WAJO - Andi Anugrah; Iwan Mamminanga; Andi Faradillah Putri (Universitas Mbojo Bima, 2023)
At this time, the government implemented an online service system (e-government). However, in an effort to develop it, it is still very far from optimal given that there is no website that is accurate for this service and the majority of people are still too unfamiliar with technology. The purpose of this study was to obtain data and information about the effectiveness of public services through the implementation of online family card services for the Atakkae Village Community at the Population and Civil Registry Office of Wajo Regency. This research was conducted using a descriptive quantitative method with a survey research type, in which the researcher took a sample from a population and used a questionnaire as a data support tool. The research population is the people who receive services in making Family Cards and live in the Atakkae Village. Data collection was carried out using observation, questionnaires and documentation, while the data analysis technique used was descriptive and statistical analysis techniques. The results of this study indicate that the effectiveness of public services through online family card services for the Atakkae Village Community at the Population and Civil Registry Office of Wajo Regency is indicated to be good in its application.